Effect of different impression methods and ceramic materials on adaptation of inlays - Rippe, Marília Pivetta; Guerra, Elen [UNESP]; Coelho, Ariannevallim Pinto [UNESP]; Anami, Lilian Costa [UNESP]; Marinho, Renata Marques de Melo [UNESP]; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (Editora Cubo, 2018)
Objective: The aim of this study was to evaluate the internal and marginal adaptation of inlays fabricated from different types of impressions (conventional and digital) and different ceramics (feldspathic and lithium disilicate). Material and Methods: Forty premolars were prepared for all-ceramic inlay restoration and assigned to 4 groups (n=10), according to the impression method (conventional with addition silicone and digital impression) and ceramic type (lithium disilicate and feldspathic ceramic blocks). For each type of impression, 10 inlays were milled from lithium disilicate blocks and the other 10 from feldspathic ceramic blocks in a CAD-CAM facility. The internal adaptation was analyzed by the replica technique. The marginal fit was analyzed under a stereo microscope by directly measuring the gap formed between the inlay and the tooth in the proximal and occlusal regions. Results: The marginal or internal adaptations were not affected by type of impression (conventional = digital impression), irrespective of the ceramic type. Only the internal adaptation was affected by the material type, i.e., feldspathic ceramic had lower values than lithium dissilicate ceramic, when considering the digital impression. Conclusion: The conventional and digital impressions promoted similar marginal and internal adaptation for feldspathic and disilicate ceramic inlays. For the digital impression the feldspathic inlays showed better internal adaptation than lithium dissilicate inlays.
Efeito de diferentes métodos de moldagem e materiais cerâmicos na adaptação de inlays
Keywords: Ceramics; Dental impression technique; Dental internal adaptation; Dental marginal adaptation